Effect of Coated Urea with Humic-Calcium on Transformation of Nitrogen in Coastal Sandy Soil: A Soil Column Method - Sulakhudin, Sulakhudin; Syukur, Abdul; Shiddieq, Dja'far; Yuwono, Triwibowo (JOURNAL OF TROPICAL SOILS, 2010)
Effect of Coated Urea with Humic-Calcium on Transformation of Nitrogen in Coastal Sandy Soil: A Soil Column Method (Sulakhudin, A  Syukur, D  Shiddieq and T  Yuwono):  In coastal sandy soil, mainly nitrogen losses due to leaching resulted to low fertilizer efficiency. Slow-release N fertilizers are proposed to minimize these losses, and humic-calcium coated urea has been examined. A soil column method was used to compare the effects of coated urea with humic-calcium on transformation and leaching loss of N in coastal sandy soil. The experiment aid to compare two kind source humic substances (cow manure and peat) which mixed with calcium as coated urea on transformation, vertical distribution and leaching N in coastal sandy soil. The concentration of humic-calcium coated urea i.e.1%, 5% and 10% based on their weight.  The results showed that urea coated with humic-calcium from cow manure (UCHM) and humic-calcium from peat (UCHP) increased the N total and available N in the soil and decreased leaching loss of N from the soil column. Compare to UCHP, UCHM in all concentration showed N-nitrate higher than N-ammonium on incubation length 2, 4 and 6 weeks. The N leached from a costal sandy soil with application coated urea with UCHM ranged from 21.18% to 23.72% of the total N added as fertilizer, for coated urea with UCHP they ranged between 21.44% and 23.25%, whereas for urea (control) reach 29.48%. Leaching losses of mineral N were lower when urea coated with UCHM compared to urea coated with UCHP or urea fertilizer.  The study concluded that the UCHM is better than UCHP in decreasing N leached from coastal sandy soil.